Prática de retextualização a partir do gênero autobiografia no eixo 5 (8⁰ e 9⁰ anos) da educação de jovens e adultos : da oralidade para a escrita - Santos, Maryluce Conceição Barros (2016)
This dissertation aims to promote a reflection about the studies that involve retextualization operations, speaking and writing, the genre autobiography and learning needs that surround the public of Youth and Adult Education. It was observed that these students reproduced speech in the text written production, without considering that each of these modalities has linguistic marks that distinguish them, making it possible to conclude that they were homogenised way of views. In order to check specific features of speech and its transformation to other relevant information written language, offered a study about the retextualization processes proposed by Marcuschi (2010). We note the linguistic behavior of students of adult education class in a retextualization activity with pedagogical adaptations related at transforming an oral text to written text in the genre autobiography. The choice of genre is the result of a more sensitive look toward the audience that was able to recognize in their own productions, compare to the other and thus form their own identity. Through a methodological approach guided in an action research, this proposal looks at the application of a didactic sequence, based on the ideas of Schneuwly and Dolz (2004), from a pedagogical notebook in order to develop the practice of retextualization so contextualized. Textual-discursive operations involved in retextualization process are demonstrated considering interactional properties with the genre autobiography. By this way, describes how students appropriate the linguistic elements that act in the oral and written language of the genre autobiography.